2011
DOI: 10.2175/193864711802721055
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Testing of a High Recovery NF/RO Integrated Treatment System for Indirect Potable Reuse

Abstract: The objective of this study was to demonstrate the viability and potential application of a high recovery NF/RO integrated treatment system concept. Compared to typically designed and operated high-pressure membrane systems, implementation of the NF/RO Integrated System could reduce the volume of concentrate that needs to be disposed of by approximately one half. The integrated treatment system concept includes a primary NF system and a secondary RO system that is used to treat concentrate produced by the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Most reverse osmosis systems use cross flow mechanism to decrease membrane cleaning periods. As the fluid flows through the reverse osmosis membranes, the downstream, remove the reject away from in concentrated reject water (brine) [33][34][35][36].…”
Section: Reverse Osmosismentioning
confidence: 99%
See 1 more Smart Citation
“…Most reverse osmosis systems use cross flow mechanism to decrease membrane cleaning periods. As the fluid flows through the reverse osmosis membranes, the downstream, remove the reject away from in concentrated reject water (brine) [33][34][35][36].…”
Section: Reverse Osmosismentioning
confidence: 99%
“…Charged nanofiltration membrane rejects ions with negative charge, such as phosphate or sulfate. Non-charged nanofiltration membrane rejects dissolved matter and uncharged in accordance of the shape and size of the molecule, while for positively charged ions, the rejection is affected by the membrane charge and according to the membrane fouling mechanism [17,32,34].…”
Section: Nanofiltrationmentioning
confidence: 99%
“…Subsequent pilot testing with two loose and low fouling NF membranes demonstrated that significant cost savings could be attained however, the major disadvantages were found to be poor rejection of nitrate, and greater number of organic contaminant detections in NF permeates compared with the RO membrane [69,133]. Due to potential advantages of using loose NF for wastewater reclamation, the Los Angeles County Sanitation District of Southern California recently conducted pilot testing of a dual NF/RO treatment process for indirect potable reuse applications using surface spreading for groundwater recharge [135]. Due to potential advantages of using loose NF for wastewater reclamation, the Los Angeles County Sanitation District of Southern California recently conducted pilot testing of a dual NF/RO treatment process for indirect potable reuse applications using surface spreading for groundwater recharge [135].…”
Section: Wastewater Treatment and Reusementioning
confidence: 99%
“…In San Diego, CA, where 85% of the water is imported, Steirer (2011) (Mansell et al, 2011). The pilot was run at 85% recovery for the primary NF system and 54% recovery for the secondary RO system, and showed that high recovery NF/RO is a viable alternative, achieving greater than 90% overall recovery.…”
Section: Mfmentioning
confidence: 99%